2019
DOI: 10.3389/fpsyt.2019.00736
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Involuntary Admissions in Patients With Severe Psychotic Disorders Treated in the ACCESS Integrated Care Model Including Therapeutic Assertive Community Treatment

Abstract: Objective: The ACCESS treatment model offers assertive community treatment (ACT) embedded in an integrated care program to patients with severe psychotic disorders. Compared to standard care, it proved to be more effective in terms of service disengagement and other outcomes in patients with psychotic disorders over 12, 24, and 48 months. Many patients with severe mental disorders experience involuntary admissions which can be potentially traumatic. In this study, we assessed the effect of ACT on reducing invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 86 publications
2
35
0
5
Order By: Relevance
“…As a result of the prevalence of suicide risk for both youth and adults in this study, OP care was less likely to be recommended at ED discharge, and ED LOS was fairly long for those needing IP admission, similar to other studies, 39,40 especially in IC cases. 31,32 However, patients who presented in police custody experienced somewhat shorter ED wait times and ED LOS, potentially reflecting providers' perceptions of the need for emergent intervention. 31,41 More research is needed to determine the relative effectiveness regarding evidence-based MH treatment and preventive care activities through telemental health compared with nontelemental health among youth and adults in the region.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result of the prevalence of suicide risk for both youth and adults in this study, OP care was less likely to be recommended at ED discharge, and ED LOS was fairly long for those needing IP admission, similar to other studies, 39,40 especially in IC cases. 31,32 However, patients who presented in police custody experienced somewhat shorter ED wait times and ED LOS, potentially reflecting providers' perceptions of the need for emergent intervention. 31,41 More research is needed to determine the relative effectiveness regarding evidence-based MH treatment and preventive care activities through telemental health compared with nontelemental health among youth and adults in the region.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, owing to the study's availability of ACT, the MH participants who had avoided or had never experienced the sometimes ''traumatic'' nature of IP IC demonstrated significantly improved severity of illness ( p = 0.004) and functional status ( p = 0.043) over time. 32 The majority (69.2%) of patients were also fully adherent to their OP treatment plan at 4-year follow-up ( p < 0.001). 32 Based on results of this study, implementation of a longitudinal study of adult and pediatric patients identified early in the rural communities as at risk for suicide could proactively serve to further inform participating rural stakeholder groups in the evaluation of targeted evidence-based structured MH OP treatment services.…”
Section: Comparative Trends In Suicide Risk and Ip Hospital Admissionsmentioning
confidence: 92%
See 3 more Smart Citations